2020
DOI: 10.1101/2020.05.08.083964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A potent neutralizing human antibody reveals the N-terminal domain of the Spike protein of SARS-CoV-2 as a site of vulnerability

Abstract: The pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory 20 syndrome coronavirus 2 (SARS-CoV-2) presents a global public health threat. Most research on therapeutics against SARS-CoV-2 focused on the receptor binding domain (RBD) of the Spike (S) protein, whereas the vulnerable epitopes and functional mechanism of non-RBD regions are poorly understood. Here we isolated and characterized monoclonal antibodies (mAbs) derived from convalescent COVID-19 patients. An mAb targeting the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 33 publications
8
63
0
1
Order By: Relevance
“…were over-represented . Other studies have also reported anti-SARS-CoV-2 mAbs derived from these genes (Brouwer et al, 2020;Cao et al, 2020;Chi et al, 2020;Ju et al, 2020;Rogers et al, 2020;Seydoux et al, 2020;Wu et al, 2020c;Zost et al, 2020).…”
Section: A Cryo-em Structure Of a Monoclonal Fab-s Protein Complex Rementioning
confidence: 95%
“…were over-represented . Other studies have also reported anti-SARS-CoV-2 mAbs derived from these genes (Brouwer et al, 2020;Cao et al, 2020;Chi et al, 2020;Ju et al, 2020;Rogers et al, 2020;Seydoux et al, 2020;Wu et al, 2020c;Zost et al, 2020).…”
Section: A Cryo-em Structure Of a Monoclonal Fab-s Protein Complex Rementioning
confidence: 95%
“…In fact, besides IGHV3-53, the only other IGHV gene that contains an NY motif in CDR H1 and an SGGS motif in CDR H2 is IGHV3-66, which is a closely-related IGHV gene to IGHV3-53 ( 32 ). As compared to IGHV3-53, IGHV3-66 has a lower occurrence frequency in the repertoire of healthy individuals (0.3% to 1.7%) ( 29 ), which may explain why IGHV3-66 is less prevalent than IGHV3-53, but yet is still quite commonly observed ( 1922, 24, 26 ) in antibodies in SARS-CoV-2 patients (Fig. 1A).…”
Section: Mainmentioning
confidence: 99%
“…3). Interestingly, a recent study identi ed a potent neutralizing human antibody that binds to the N-terminal domain of SARS-CoV-2 S 36 . Although this antibody does not bind to the RBD or block its interaction with ACE2, its neutralizing activity was much higher than that of antibodies targeting the RBD 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study identi ed a potent neutralizing human antibody that binds to the N-terminal domain of SARS-CoV-2 S 36 . Although this antibody does not bind to the RBD or block its interaction with ACE2, its neutralizing activity was much higher than that of antibodies targeting the RBD 36 . This report highlights the importance of the N-terminal domain of SARS-CoV-2 S during viral infection and may support the important role of AXL during infection of the human pulmonary and bronchial systems.…”
Section: Discussionmentioning
confidence: 99%